Inhibition of Radioactive Depletion of Hemocytes and Antitumor Effects of Flavonoid - Gu, Yeun-Hwa; Yamashita, Takenori; Inoue, Tota; Kang, Ki-Mun (Archives of Clinical and Medical Case Reports, 2021)
Natural products are able to inhibit radiation effects and exert an antitumor effect with fewer adverse reactions; however, their antitumor effects are less than those of widely-used synthetic drugs. Flavonoid is a natural material that has attracting attention, and we extracted this material with alcohol and investigated the effect of continuous flavonoid administration on radioactivity-induced reduction of hemocytes, in addition to the antioxidant and antitum or effects of flavonoid. Following a 1-week adjustment period, flavonoid was administered intraperitoneally to male ICR mice at a dose of 100 mg/kg every other day for 2 weeks. Following administration, 2 Gy whole-body irradiation was performed and the counts of leukocytes, lymphocytes, and granulocytes and monocytes in the peripheral blood were determined 1, 3, 7, 15 and 30 days after irradiation. These cells were considered since they are closely associated with immunity to radioactivity. In a second experiment, flavonoid was similarly administered to the mice for 2 weeks after a 1-week adjustment period, and 2 Gy whole-body irradiation was performed. The antioxidant effects in hemocytes were then investigated using 2,2'-azobis (2-amidinopropane) dihydrochloride (AAPH), a radical generator. In a third experiment, 1×106 Sarcoma-180 cells were inoculated into the right thigh of mice, which were divided into four groups: control, flavonoid-treated, 6 Gy irradiated and Flavonoid-treated + 6 Gy irradiated groups, and changes in tumor size were measured for 20 days. Statistical analysis was conducted using ANOVA for multiple groups. In the three experiments, administration of Flavonoid inhibited the reduction of hemocytes caused by whole-body irradiation, showed antioxidant effects against radioactivity, and inhibited tumor growth, respectively. In conclusion, our data suggest that the anti